Model Tarikan dan Bangkitan Pergerakan Transportasi Bundaran Suci Akibat Aktivitas Citimall Garut - Ersa Hermalia Sukma; Ida Farida (Jurnal Konstruksi, 2026)
Garut Regency has experienced significant population growth, leading to increased transportation demand that potentially causes congestion, particularly at Bundaran Suci. This study aims to analyze the operational impact of Citimall Garut on traffic conditions at Bundaran Suci, focusing on trip generation and attraction. Using a quantitative approach with the Trip Rate Analysis method and referring to the 2023 Indonesian Highway Capacity Manual (PKJI), the research compares traffic volumes before and after the mall's operation. The findings reveal a significant rise in vehicle volume, especially on Thursdays, with the highest trip rate recorded at 3.45 pcu/hour for inbound vehicles and 2.53 pcu/hour for outbound vehicles. Bundaran Suci has reached a high level of saturation, with all links exceeding the standard saturation degree (>0.85). The level of service is categorized as E, indicating an average delay of 49 seconds per pcu and a queuing probability of up to 147%. Additionally, the parking capacity at Citimall Garut is deemed insufficient, further aggravating traffic conditions in the surrounding area. To address these issues, the study recommends increasing the mall’s parking capacity and implementing better traffic management strategies at Bundaran Suci. It also urges local authorities to improve transportation infrastructure to mitigate the negative traffic impacts caused by activities at Citimall Garut. These steps are necessary to maintain smooth traffic flow and prevent further congestion in the area.